Purification and properties of cephalosporinase in Escherichia coli. - Minami, S (1980)
Cephalosporin beta-lactamase (cephalosporinase) was purified from a strain of Escherichia coli resistant to beta-lactam antibiotics. The purified enzyme preparation gave a single protein band on polyacrylamide gel electrophoresis, and its molecular weight was 39,000 from sodium dodecyl sulfate-acrylamide gel electrophoresis. Its isoelectric point was 8.7. The specific activity was 31.7 mumol/min per mg of protein of the purified enzyme for the hydrolysis of cephaloridine. The optimal pH was about 8.0, and the optimal temperature was 36 degrees C. The enzyme activity was inhibited by iodine, some divalent metallic ions, semisynthetic penicillins, cefuroxime-type cephalosporins, and cephamycin derivatives. The enzymological properties of the purified preparation have been compared with those of beta-lactamases from other gram-negative bacteria.